Association Between ALDH-2 rs671 and Essential Hypertension Risk or Blood Pressure Levels: A Systematic Review and Meta-Analysis - Zheng, Yawei; Ning, Cheng; Zhang, Xingxing; Zhao, Yuhao; Li, Yizhuo; Qian, Lichao; Li, Jie; Fang, Zhuyuan (Frontiers in Genetics, 2020)
Background: The association between Aldehyde dehydrogenase II (ALDH-2) rs671 polymorphism and essential hypertension (EH) risk or blood pressure (BP) levels remains unclear. Objective: To systematically review the influence of the aldehyde dehydrogenase II rs671 polymorphism on essential hypertension risk and blood pressure levels. Methods: The PubMed, EMbase, Web of Science, Cochrane Library, CNKI and CBM databases were electronically searched to identify case-control or cohort studies published prior to July 2019 that examined the association between the rs671 polymorphism and the risk of essential hypertension or blood pressure levels. A meta-analysis was conducted with Stata 15.1 software. Results: Twenty-two articles were included. Among these articles, 20 incorporated 30 individual studies evaluating the association between the rs671 polymorphism and EH (11,051 hypertensive patients and 15,926 normotensive controls), and 8 incorporated 12 individual studies evaluating the association between the rs671 polymorphism and BP (20,512 subjects). The results of the meta-analysis showed that the mutation of the rs671 polymorphism was associated with a significantly decreased risk of EH in all models: allelic model (OR = 0.80, 95% CI: 0.73–0.87), homozygous model (OR = 0.71, 95% CI: 0.63–0.80), heterozygous model (OR = 0.79, 95% CI: 0.72–0.87), dominant model (OR = 0.79, 95% CI: 0.71–0.87), and recessive model (OR = 0.76, 95% CI: 0.68–0.85). In the stratified analyses, significant associations were found for males, drinkers and population-based studies. Simultaneously, the A carriers had lower SBP (WMD = −1.78, 95% CI: −3.02 to −0.53) and DBP (WMD = −1.09, 95% CI: −1.58 to −0.61) levels than individuals with the GG homozygote. Conclusion: The collective findings of this meta-analysis suggested that the ALDH-2 rs671 polymorphism represented an important genetic marker in the development of hypertension. Considering the overall quality of evidence and the relatively small pooled sample size, more well-conducted high-quality studies are required to verify the above conclusion. Systematic Review Registration Number: PROSPERO (CRD42019129746).